Anti-cancer and antimicrobial efficacy of ZnO nanoparticles synthesized via green route using Amaranthus dubius (Spleen Amaranth) leaves extract - Faaiza Naaz K; Alavya Tiwari; Aabid Hussain Shaik; Indumathi P; Brianna Brianna; Ayaz Anwar; Mohammed Rehaan Chandan (Green Chemistry Letters and Reviews)
Green synthesis of nanomaterials is eco-friendly, cost effective approach. This work reports anti-cancer and antimicrobial properties of ZnO nanoparticles synthesized via green route using Amaranthus dubius leaf extract. XRD analysis confirmed the formation of highly pure ZnO nanoparticles with increased crystallinity, exhibiting a particle size of ∼14 nm. The FTIR spectra indicated the formation of ZnO nanoparticles with distinct bands in the 400 and 600 cm−1 range, while SEM images revealed spherical-shaped nanoparticles, along with some flower-like structures, indicating a higher surface-to-volume ratio. The synthesized nanoparticles exhibited higher antimicrobial effects at 50 μg/mL with a maximum inhibitory zone diameter of 22 mm observed for B. cereus and 10 mm for S. aureus, E. coli, and Salmonella spp. Anti-cancer effects were evaluated against CCD112 normal colon cell line and HCT116 colorectal cancer cell line. The results demonstrated that ZnO nanoparticles were non-toxic to the normal cell line. At a concentration of 7.82 μg/mL, there was a 15.4% decrease in cell viability relative to the control in HCT116 cell lines, indicating cytotoxicity. At 125 μg/mL, the cells exhibited extreme cytotoxicity against cancer cell lines, with a viability of only 87.66%, showing a 12.3% decrease compared to the control.